Influence of the surgical technique on survival in the treatment of carcinomas of the true cardia (Siewert Type II) - Right thoracoabdominal vs. transhiatal-abdominal approach. Issue 3 (March 2019) - Tosolini, C.; Reim, D.; Schirren, R.; Feith, M.; Friess, H.; Novotny, A.R.
Abstract: Introduction: It is still a matter of debate whether subtotal esophagectomy via a right thoracoabdominal approach (RTA) or extended gastrectomy using a transhiatal-abdominal approach (TH) is the favorable technique in the treatment of Siewert type II esophago-gastric junction adenocarcinoma (EJA). Materials and methods: Patients undergoing RTA or TH for EJA at our institution between 2000 and 2013 were extracted from a prospective database. Of 270 patients 91 (33.7%) underwent RTA and 179 (66.3%) were treated by TH. Differences in baseline characteristics, 30d mortality and complications were investigated using the χ2-test or exact testing. Survival analysis was performed using the Kaplan-Meier method and log rank testing. Median survival and hazard ratios were calculated and multivariable analysis of predictors was performed using a Cox model. Confounders were balanced using propensity score matching (PSM). Results: No significant difference between the two procedures was detected regarding overall-survival (OS) and disease-free survival (DFS). 30d mortality rates were 1.1% in the RTA group and 4.5% in the TH group (p = 0.134). Morbidity was 34.1% in the RTA and 24.6% in the TH group (p = 0.006). Cox regression analysis identified age, ASA class and UICC stage as independent prognostic factors for OS. After PSM survival curves (OS + PFS) showed no significant difference. Conclusion: The present study could not detect a difference between RTA and TH from the oncologic point of view; RTA was not associated with higher 30d mortality. RTA for Siewert Type II EJA is justified whenever the oral tumor margin cannot be safely reached via a transhiatal approach. Abstract : SYNOPSIS: Outcomes of transthoracic esophagectomy or extended gastrectomy through a transhiatal-abdominal approach for adenocarcinoma of the cardia were compared. Both procedures are oncologically equivalent. The indication for abdominothoracic approach is dictated by the luminal extension of the tumor into the distal esophagus.